Longitudinal Associations Between Food Insecurity and Suicidal Ideation Among Adults Aged ≥65 in the Korean Welfare Panel Study - Jeongyoon Lee; Tae-Young Pak (Frontiers Media S.A., 2023)
Objectives: This study aimed to explore longitudinal associations between food insecurity and suicidal ideation, and the moderating roles of intervention programs.Methods: Data were derived from the 2012-2019 waves of the Korean Welfare Panel Study. Participants aged ≥65 at baseline (n = 4,425) and their annual follow-up measurements for a mean of 6.58 years were included. Conditional fixed effects logistic regressions were used to test 1) associations between food insecurity and the onset of suicidal ideation; 2); whether associations were attenuated by food assistance and income support programs.Results: Food insecurity was associated with higher odds of suicidal ideation in the full sample (OR, 1.77; 95% CI, 1.37-2.29), among women (OR, 1.67; 95% CI, 1.24-2.26) and men (OR, 2.06; 95% CI, 1.25-3.40). The association between food insecurity and suicidal ideation was attenuated by participation in home-delivered meal services (OR, 0.43; 95% CI, 0.21-0.88).Conclusion: Food insecure older adults were more likely to consider committing suicide than their food secure counterparts. Food assistance through home-delivered meal services, but not other intervention programs, could weaken this link.